O uso das mídias sociais nas eleições e seus efeitos no contexto dos eleitores - Santana, Davi Pinheiro de (2021)
The object of this dissertation is about the use of social media and its effects in the context of treatments, since it involves a good part of the research, since social networks and struggles are related to politicians. The work is divided into two articles. We then looked for a moment, and the research that was presented on the proposal of years 2008 and 202, exploring two Scopus Web of Science databases. The results that are, the authors were the main subjects studied and journals. The articles tend to investigate phenomena such as participation, and involvement, the studies studied have as their main objective the studies, that is, the investigation trend, the understanding of opinion aspects, among others. It was a research project whose objective was to verify how the dissemination of social policy, regarding our opinion of Z.'s interest in correlational, exploring aspects present in social media such as an exposure of information, connection with politicians and heterogeneity of network, relating them to the opinion of the actors. In view of this, an online questionnaire was applied7 with 3 respondents. The results were analyzed through modeling by opinion information, which presented an information fit with information from the exposure by the opinion of the representatives, which since the opinion of the opinion is informed by information that the individual receives based on the their relationships. The heterogeneity factor influences the influence of a relevant network, however, it also affects the opinion that influences the relationship of a significant network.